Implementation of Finger Print Absence in Employee Work Discipline at SD Muhammadiyah 7 Bandung City - Hamdani, Dadan; Hidayati, Dian (Mudir : Jurnal Manajemen Pendidikan, 2023)
The current developments that are increasingly developing and advancing have a lot of impact on the sophistication of technology. systems that used to be manual are now electronic, such as fingerprint-based electronic attendance. Likewise, the application of Finger Print attendance at SD Muhammadiyah 7 schools is very appropriate in order to improve the work discipline of employees at school. With fingerprints, employees don't just go to and from school as they please, the benefits of having fingerprints indirectly educate employees so that they have work discipline, the benefits of disciplined work are our productivity and service to our consumers at institutions will run well and optimally. In carrying out its implementation, apart from fingerprinting, SD Muhammadiyah 7 schools also apply manual absences as well to avoid damage or problems with the machine. With the implementation of this finger print absence, employee discipline at SD Muhammadiyah 7 increases, employees are in an orderly manner when entering and leaving work at school in accordance with the schedule set by the school. Employees who cannot print their finger due to illness, assignments from school, and other matters are sufficient to provide evidence and report to the designated school to provide an explanation.